Importance of global co-innovation networks: A TCS case study - Zutshi, Aneesh (2009)
Today all kinds of innovations and research work is done by partnerships of competent entities each having some specialized skills. Like the development of the global economy, global innovation partnerships have grown considerably and form the basis of most of the sophisticated innovations today. To further streamline and simplify such cooperation, several innovation networks have been formed, both at local and global levels. This paper discusses the different types of innovations and how cooperation can benefit innovation in terms of pooling of resources and sharing of risks. One example of an open global co-innovation network promoted by Tata Consultancy Services, the TCS COIN is taken as a case. It enables venture capitalists, consultants, research agencies, companies and universities form nodes of the network so that each entity can play a meaningful role in the innovation network. Further, two innovation projects implemented using the COIN are discussed. Innovation Networks like these could form the basis of a unique global innovation network, which is not owned by any company and is used by innovation partners globally to collaborate and conduct research and development.